Indonesian Cross-Culture Validation and Psychometric Testing of The Nurses’ Occupational Stressor Scale 21 (Noss-21) Questionnaire - Hidayati, Rizqi Wahyu; Nirmalasari, Novita; Sari, Ike Wuri Winahyu (JENDELA NURSING JOURNAL, 2025)
Background: Currently, many nurses experience stress because they have a lot of work. Even though the impact of stress on nurses can affect health services to patients. Therefore, a tool is needed to measure the level of stress at work in nurses.Purpose: The purpose of this research is to transcribe and cross validate the NOSS-21 into Indonesian, and conduct psychometric tests on nurses in Indonesia.Methods: The study used quantitative methods. This study used Brislin's Classic Model for translation and validation. Tests conducted using Pearson product moment and Cronbach Alpha as a construct test. The sample used amounted to 168 nurses who worked for at least 1 year in Islamic hospitals in Yogyakarta. Respondents who were excluded were nurses who worked in polyclinics and pediatric wards.Result: Based on the results, the average value of I-CVI is 1.00, while based on the Pearson product moment test, it can be seen that 18 items are considered valid and 3 items are invalid. Although 3 items were invalid, but based on the importance of the questionnaire domain, the researcher decided to include these 3 items in the study. The reliability of the questionnaire is strongly reliable as the value is 0.899.Conclusion: The Indonesian Nurses' Occupational Stressor Scale 21 (INOSS-21) questionnaire can be used as a questionnaire to measure nurses' occupational stress. The limitation of this study is that the study respondents were only from Islamic hospitals. In addition, not all nurses were included in the study, for example, polyclinic and pediatric ward nurses were excluded.